PENGARUH MEDIA POSTER DAN POWER POINT TERHADAP PENGETAHUAN LANSIA TERKAIT COVID-19 DI KOTA SEMARANG - Kodir Kodir; Novita Wulan Sari; Margiyati Margiyati; Nur Sholiha Rositayani (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2021)
The elderly group during the pandemic is the group most at risk of experiencing severity/morbidity and mortality due to Covid-19 disease. This is because elderly patients (geriatric) generally have various comorbidities, such as cardiovascular disease, chronic respiratory disease, diabetes mellitus and hypertension. The elderly as a vulnerable group, of course, really need the right information related to Covid-19 with the right media. Media that can be used to provide information on Covid-19 to the elderly are posters and power points. This provision can be done by nurses. This research will be conducted on 50 elderly people at Kelurahan Bendungan Semarang. The study was conducted by measuring the level of knowledge with a knowledge level questionnaire about the problem of covid-19, before and after treatment. The design of this study was a quasi-experimental pre-test post-test with control group. The research sample was determined by total sampling with certain criteria, namely: 1) elderly aged 60 years and over, 2) can read, write, communicate well, 3) do not experience sensory, cognitive, and movement disorders, 4) participate in all activities with 100% attendance. The division of the group was 25 people for the intervention group and 25 people for the control group. The provision of posters and PPT media was held 4 times in 4 weeks. This is done in combination because the combination of the two media can increase the level of better knowledge, especially for the elderly who have experienced a decline in function. There is an increase in the level of knowledge from low level 4 people (16%), medium level 15 people (60%), high level 6 people (24%) to low level 1 person (4%), medium level 9 people (36%), high level 15 people (60%).